2005
DOI: 10.1088/0953-4075/38/18/007
|View full text |Cite
|
Sign up to set email alerts
|

Spin asymmetries in elastic and inelastic scattering from rubidium

Abstract: Experimental and theoretical results are presented for the A2 spin asymmetry for elastic and inelastic scattering of spin-polarized electrons from rubidium, at incident electron energies of 15, 20, 30, 50 and 80 eV. Theoretical calculations are performed within a semi-relativistic Breit-Pauli R-matrix (close-coupling) model. The experimental data reveal significant asymmetries at all energies. The experimental results are reasonably well described by the present theoretical calculations and by other calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Spin-asymmetry function A 2 for electron-impact excitation of the (5s) 2 P 1/2 → (5p) 2 P 1/2,3/2 transitions in Rb at an incident electron energy of 20 eV. The BP37 results for the individual fine-structure levels are shown in comparison to those obtained if the fine-structure is not resolved, as is the case in the measurements of Went et al [20] and Guinea et al [9]. a shift in the zero crossing between our results and the experimental data.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Spin-asymmetry function A 2 for electron-impact excitation of the (5s) 2 P 1/2 → (5p) 2 P 1/2,3/2 transitions in Rb at an incident electron energy of 20 eV. The BP37 results for the individual fine-structure levels are shown in comparison to those obtained if the fine-structure is not resolved, as is the case in the measurements of Went et al [20] and Guinea et al [9]. a shift in the zero crossing between our results and the experimental data.…”
Section: Resultsmentioning
confidence: 80%
“…The principal purpose of the present study was to provide theoretical support to an ongoing study in the Brisbane group. Most of our results, for elastic and inelastic electron scattering from Rb atoms for incident energies between 15 eV and 80 eV, will therefore be presented in a joint paper by Guinea et al [9]. Here, we only pick one collision energy (20 eV) and the inelastic 5s → 5p transition to illustrate the sensitivity of various predicted observables to the details of the computational model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two theoretical approaches are presented here: a semi-relativistic Breit-Pauli R-matrix approach, with and without pseudostates, and a fully relativistic Dirac-Fock calculation. The first approach is a calculation by Bartschat; for details see Guinea et al [8]. The second is that of Stauffer [9].…”
Section: Resultsmentioning
confidence: 99%
“…Corresponding Distorted-Wave Born Approximation (DWBA) results were calculated originally by Pangatiwar and Srivastava [5], later updated by Saxena and Srivastava [6], and results from an even later Relativistic Distorted-Wave (RDW) approximation calculation from Zeman et al [7] are also noted. Superelastic electron scattering from the resonance line has also been investigated by Hall et al [8], while asymmetries in the scattering of spin-polarized electrons from Rb were studied by Guinea et al [9]. A theoretical analysis of channel coupling and relativistic effects in the excitation of the Rb resonance line by Payne et al [10], using a Breit-Pauli (BP) R-matrix (close-coupling) method, has also been reported.…”
Section: Introductionmentioning
confidence: 99%